The Presence of Audit Committee Improves Transparency In Financial Reporting Process: Comparison between Merged and Unmerged FTSE 100 Companies - Pasupathi, Swarna (2006)
Corporate Governance is often considered as a system by which companies are directed and controlled whose primary role is to safeguard the investor's wealth. This research has outlined the literature which initiated the need for governance in companies which has slowly led to the formation of standard regulatory codes in the United Kingdom. The impact recent reforms in the governance code and their emphasis on Audit Committee's roles have been observed. The highlight of this study is to discover the relationship between the existence of audit committee in the company's board and the quality of financial reporting process. The presence above relationship is monitored and compared between the merged and unmerged firms across different sectors. The analysis of their annual reports suggests the fact that the presence of audit committee with financial expertise gains reputation among the company's finance director, internal auditors and External auditors. This increases the level of scrutiny involved during the financial reporting process thereby increasing its quality and transparency.